Faktor Determinan Kualitas Lingkungan di Provinsi Jambi - Osi Hayuni Putri; Mira Hastin; Masrida Zasriati; Dewi Ernita (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The rapid increase in economic activity in Jambi Province over the past two decades has placed significant pressure on environmental quality. The growth of GRDP, driven by extractive sectors, population growth, intensive energy consumption, the growth of motorized vehicles, the diverse quality of human resources (HR), and the rise of Foreign Direct Investment (FDI), are important factors influencing environmental conditions. This study aims to analyze the determinants of environmental quality in Jambi Province using these economic and social development variables. The study uses a descriptive-analytical approach with secondary data from various agencies. The results show that economic growth, fossil fuel consumption, and the growth of motorized vehicles have a strong influence on environmental degradation. Population growth affects the environment through pressures on land, energy, and transportation needs. The quality of human resources plays a positive role in improving environmental quality, while FDI has a dual impact depending on the investment sector. This study provides policy recommendations for realizing sustainable development in Jambi Province.